Context Matters : a qualitative study of social innovation in rural Sweden - Bengtsson, Amanda (SLU/Dept. of Urban and Rural Development, 2020)
Recently, the concept of social innovation has gained increased attention both in academia and in policy, presented as a useful tool for solving complex societal challenges, also the societal challenges apparent in rural areas. The rural context, however, and its implications for social innovation, is often neglected. This study sets out to increase knowledge about the interplay between social innovation and the rural context by exploring how the context of rural Sweden constrains or enables social innovation, and how the assets and liabilities of the context are utilised or overcome. The empirical cases are five social innovation initiatives in rural locations across Sweden. The study finds that different dimensions of context enable or constrain social innovation to a varying extent throughout the process. In line with previous research, the social context appears to enable social innovation while the institutional context constitutes the main liability. Extra-local networks and individuals are found to be crucial to overcome such constraints. In sum, this study contributes to the field of rural development by underscoring the matter of context and the need for governmental action in order to release the potential of social innovation as a tool for solving rural societal challenges.